A Review of Global Climate Change Protocols and International Conferences: Progress, Challenges, and Future Directions - Asif Bashir; Rico Nur Ilham; Naseer Ahmad Bhat (RADJA PUBLIKA, 2025)
This review offers an incisive and critical appraisal of the evolution, efficacy, and limitations of global climate change protocols and international climate diplomacy, with a particular focus on the United Nations Framework Convention on Climate Change (UNFCCC) and the Conference of the Parties (COP) mechanisms. Anchored in the latest scientific consensus from the Intergovernmental Panel on Climate Change (IPCC) and the World Meteorological Organization (WMO), the paper underscores the anthropogenic causality of global warming and delineates the observed and projected ramifications of climate perturbations on ecological stability, socioeconomic systems, and geopolitical equilibriums. Through a methodical examination of landmark accords—from the legally binding architecture of the Kyoto Protocol to the voluntary, nationally determined contributions under the Paris Agreement and the transformative aspirations of the Glasgow and Dubai declarations—this review delineates the metamorphosis of climate governance from rigid legalism to adaptive multilateralism. The study interrogates the efficacy of climate finance instruments, notably the Green Climate Fund, and scrutinizes barriers to equitable technology transfer, institutional transparency, and implementation fidelity, particularly in the Global South. It also elucidates region-specific vulnerabilities with a granular analysis of South Asia and the ecologically fragile Kashmir Valley, revealing the disproportionate burdens borne by climate-fragile geographies. Moreover, it interrogates the persistent North–South dichotomy, operational inertia, and political obstructions that thwart comprehensive climate action. Finally, the review advocates for a reinvigorated climate governance paradigm premised on inclusive multilateralism, innovation-driven adaptation, and equity-oriented accountability. It concludes that transformative ambition—grounded in justice, resilience, and scientific integrity—must now supplant incrementalism to avert climate catastrophe and forge a sustainable planetary future.